Biosecurity in nursing in times of covid-19 in emergency services - Paucar Ignacio, Yordy (2024)
Objective: To describe and understand the experiences in compliance with biosafety measures by COVID-19 in nurses at a Public Hospital in Chiclayo, Peru. Method: The study was qualitative with a phenomenological approach. The study subjects were made up of 12 nurses from Hospital Las Mercedes; The sample was non-probabilistic, for convenience and saturation, having as inclusion criteria: nurses who worked in the emergency service from March to June 2020 and having signed the informed consent. Nurses on leave for health or maternity reasons were excluded. The information collection instrument was the online in-depth semi-structured interview. In the research process, ethical principles and scientific rigor were considered. Results: Four propositions were obtained: Connotation of experiences as expressions in the work on biosafety in emergencies; the biosecurity practiced by nurses in defense of life, insufficient biosecurity measures: safe contagion and death, relearning to live in a pandemic from the personal, family and work aspects in the face of biosecurity measures. General conclusion: The experiences of the nurses regarding biosafety measures have been of great connotation, suffering, fear, uncertainty and learning; which have been overcome as the months have passed, proving to be a fundamental pillar in managing the pandemic.